2010
DOI: 10.1016/j.juro.2009.12.106
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Amitriptyline on Symptoms in Treatment Naïve Patients With Interstitial Cystitis/Painful Bladder Syndrome

Abstract: Background-Amitriptyline is frequently used to treat patients with IC/PBS. The evidence to support this practice is derived mainly from a small single site clinical trial and case reports.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
111
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 157 publications
(113 citation statements)
references
References 20 publications
(14 reference statements)
0
111
2
Order By: Relevance
“…78,79 Two RCTs have demonstrated a benefit of amitriptyline over placebo. 57,80 Van Ophoven et al 80 reported a statistically significant improvement in O'Leary-Sant IC symptom and problem index scores from baseline in patients treated with amitriptyline vs. placebo (p=0.05). Overall, 63% vs. 4% of the treatment group vs. placebo group were considered significantly improved at four months followup.…”
Section: Amitriptyline (Option Grade B)mentioning
confidence: 99%
See 2 more Smart Citations
“…78,79 Two RCTs have demonstrated a benefit of amitriptyline over placebo. 57,80 Van Ophoven et al 80 reported a statistically significant improvement in O'Leary-Sant IC symptom and problem index scores from baseline in patients treated with amitriptyline vs. placebo (p=0.05). Overall, 63% vs. 4% of the treatment group vs. placebo group were considered significantly improved at four months followup.…”
Section: Amitriptyline (Option Grade B)mentioning
confidence: 99%
“…Significant improvement in 45-50% of patients may be expected with only advice and support, as demonstrated in two well-designed, randomized trials. 57,58 Bosch et al have developed a practical IC/BPS standard advice checklist to insure all healthcare topics are discussed with the patient. 58 Up to 90% of patients have exacerbations of their symptoms after ingesting certain foods or drinks.…”
Section: Patient Education (Recommended In All Patients Grade A) Andmentioning
confidence: 99%
See 1 more Smart Citation
“…73 They function to increase norepinephrine and serotonin levels and exhibit anticholinergic and direct muscle relaxant effects on the urinary bladder. 73,74 HEREDITARY PERIPHERAL NEUROPATHIES Hereditary peripheral neuropathies are genetically and phenotypically heterogeneous disorders. Charcot-Marie-Tooth (CMT) disease is the most common inherited peripheral neuropathy.…”
Section: Hiv-associated Neuropathymentioning
confidence: 99%
“…A systematic review 47 of two randomised controlled trials (RCTs) 48,49 that included a total of 281 patients who were treated with increasing titrated doses of amitriptyline between 10 mg and 100 mg over a 4-month period showed trends in improvement in urinary urgency, frequency and pain scores in both trials compared with nontreated patients. However, these were only statistically significant in the smaller study of 48 patients.…”
mentioning
confidence: 99%